Using a New Landmark of the Most External Point in the Embolization of Distal Anterior Choroidal Aneurysms: A Report of Two Cases - Zhang, Nai; Xin, Wen-qiang; Yue, Shu-yuan; Zhong, Yue; Wei, Wei; Yang, Xin-yu; Wang, Zi-jun; Xiao, Fu-shun (Frontiers in Neurology, 2020)
ABSTRACT There are landmarks on the course of the anterior choroidal artery (AChoA), such as the original point (OP) and the plexal point (PP), as documented in previous articles. In these previous articles, the AChoA was the terminal branch of the internal carotid artery (ICA), which had 2 segments throughout its course. The first cisternal segment began from the origin and ended at the point where the artery reached the choroidal fissure (the PP). The second segment consisted of one or more branches, which passed through the choroidal fissure and entered the choroid plexus. However, we found another angiographic landmark, named the most external point (MEP), along the course of the AChoA in the anteroposterior (AP) view. There was a sharp turn at the outermost limit of the course of the AChoA, and then the AChoA progressed inward and upward. We defined the outermost limit as the MEP of the AChoA. This study describes two rare cases of distal AChoA aneurysms associated with arteriovenous malformation (AVM) and Moyamoya disease that developed intraventricular haemorrhage, and we used the parent artery occlusion (PAO) technique to embolize the distal AChoA lesions at the MEP. The patients recovered well without any neurological complications.